Giant prolactinoma mimicking low-tension glaucoma at presentation. (6th February 2015) - Karl, David; Gillan, Stewart Neil; Goudie, Colin; Sanders, Roshini
Abstract : We describe a case of a 68-year-old man, referred by his optometrist with suspected low-tension glaucoma, who presented with advanced cupped optic discs and field of vision loss that were subsequently found to be due to a giant prolactinoma. Failing vision in low-tension glaucoma suspects should have a low threshold for neuroimaging.